Interval Type-2 Fuzzy Gain-adaptive Controller Of A Doubly Fed Induction Machine (dfim) - Loukal, K.; Benalia, L. (University of Eloued جامعة الوادي, 2016)
This paper presents a comparison between an Interval Type-2 Fuzzy Gain-Adaptive IP (IT2FGAIP) controller and a conventional IP controller used for speed control with a direct stator flux orientation control of a doubly fed induction motor. In particular, the introduction part of the paper presents a Direct Stator Flux Orientation Control (DSFOC), the first part of this paper presents a description of the mathematical model of DFIM, and an adaptive IP controller is proposed for the speed control of DFIM in the presence of the variations parametric, A interval type-2 fuzzy inference system is used to adjust in real-time the controller gains. The obtained results show the efficacy of the proposed method.
Articale in Journal of fundamental and Applied Sciences Vol. 08, N. 02
Keywords: Doubly fed induction motor; DFIM; direct stator flux orientation control; interval type-2 fuzzy gain-adaptive IP controller; IT2FGAIP; IP controller.